Confluence of Depression and Acute Psychological Stress Among Patients With Stable Coronary Heart Disease: Effects on Myocardial Perfusion. Issue 6 (30th October 2014) - Burg, Matthew M.; Meadows, Judith; Shimbo, Daichi; Davidson, Karina W.; Schwartz, Joseph E.; Soufer, Robert
Abstract : Background: Depression is prevalent in coronary heart disease (CHD) patients and increases risk for acute coronary syndrome (ACS) recurrence and mortality despite optimal medical care. The pathways underlying this risk remain elusive. Psychological stress (PS) can provoke impairment in myocardial perfusion and trigger ACS. A confluence of acute PS with depression might reveal coronary vascular mechanisms of risk. We tested whether depression increased risk for impaired myocardial perfusion during acute PS among patients with stable CHD. Methods and Results: Patients (N=146) completed the Beck Depression Inventory‐I (BDI‐I), a measure of depression linked to recurrent ACS and post‐ACS mortality, and underwent single‐photon emission computed tomography myocardial perfusion imaging at rest and during acute PS. The likelihood of new/worsening impairment in myocardial perfusion from baseline to PS as a function of depression severity was tested. On the BDI‐I, 41 patients scored in the normal range, 48 in the high normal range, and 57 in the depressed range previously linked to CHD prognosis. A BDI‐I score in the depressed range was associated with a significantly greater likelihood of new/worsening impairment in myocardial perfusion from baseline to PS (odds ratio =2.89, 95% CI: 1.26 to 6.63, P =0.012). This remained significant in models controlling ACS recurrence/mortality risk factors and medications. There was no effect for selective serotonin reuptake inhibitor medications. Conclusions: Depressed patients with CHD are particularly susceptible to impairment in myocardial perfusion during PS. The confluence of PS with depression may contribute to a better understanding of the depression‐associated risk for ACS recurrence and mortality.